Formation, Rotation, and Present-Day Configuration of Kashmir and Peshawar Basins in NW Himalaya - Shah, Afroz Ahmad; Abd Manan, Nurhafizah; Aliudin, Nurul Afiqah Binti; Cahyaningsih, Catur; Batmanathan, Navakanesh M.; Malik, Javed N. (Frontiers in Earth Science, 2020)
The thrust top intermontane basins that are located to the east of the Hazara-Kashmir Syntaxis (HKS) in NW Himalaya are ~NW-SE oriented and run parallel to the strike of the major Himalayan thrusts, which is in contrast to the similar basins that lie at the west of HKS (e.g. Peshawar basin). Although these basins are similar in age yet their structural orientation differs, which has not been previously investigated in much details. Therefore, here we investigate the structural details using the 30m shuttle topography, regional seismicity, earthquake centroid moment tensors (CMT) solutions, previously published works, and geological fieldwork at Anantnag, Kashmir, where bedrock geology and Plio-Pleistocene to Holocene sediments are mapped. The three tectonic model for the formation of Kashmir basin are investigated and new data are produced to refine the existing knowledge on the formation of Kashmir and Peshawar basins. Our results establish that Kashmir basin is definitely neither a pull-apart basin nor a rift basin, and we reinforce that the basin can be formed in a piggyback structural style. We demonstrate that intermontane basins on either of HKS have rotated during their evolutionary journey. The estimated >45° clockwise rotation of Kashmir basin is in contract to the < 45° anticlockwise rotation of the Peshawar basin, and this rotation coincides with the emergence of the >120 km long left-lateral strike-slip fault, the Jhelum fault (JF), which has dominantly left-lateral strike-slip movement at north, and oblique in south. We show that the JF largely controls the formation rotation and the present configuration of regions on either side of the HKS. The published paleomagnetic data supports our results and show that basin formation, lateral extent, geometry, and rotation are controlled by faulting where the emergence of the Main Boundary Thrust (MBT) fault system seems to have largely controlled the formation and lateral extent of the Kashmir basin, while as the JF has contributed towards the translation, rotation and present structural configuration of the intermontane basins in the region.